The Law on negotiable instruments : with documents of title - De Leon, Hector S.; Hector M. De Leon, Jr. (Manila, Philippines : Rex Book Store, 2013)
This book discusses at some length the Civil Code provisions on documents of title and the Warehouse Receipts Law which are included in the study of the subject.
Part 1 The negotiable instruments law -- Title I Negotiable instruments in general -- Title II Bills of exchange -- Part II Documents of title -- Chapter I The issue of warehouse receipts -- Chapter 2 Obligations and rights of warehousemen upon their receipts -- Chapter 3 Negotiation and transfer of receipts -- Chapter 4 Criminal offenses -- Chapter 5 Interpretation
Keywords: NEGOTIABLE INSTRUMENTS